Management of achalasia cardia: Expert consensus statements. Issue 8 (11th July 2018) - Ramchandani, Mohan; Nageshwar Reddy, D; Nabi, Zaheer; Chavan, Radhika; Bapaye, Amol; Bhatia, Shobna; Mehta, Nilay; Dhawan, Pankaj; Chaudhary, Adarsh; Ghoshal, Uday C; Philip, Mathew; Neuhaus, Horst; et al.
Abstract: Achalasia cardia (AC) is a frequently encountered motility disorder of the esophagus resulting from an irreversible degeneration of neurons. Treatment modalities are palliative in nature, and there is no curative treatment available for AC as of now. Significant advancements have been made in the management of AC over last decade. The introduction of high resolution manometry and per‐oral endoscopic myotomy (POEM) has strengthened the diagnostic and therapeutic armamentarium of AC. High resolution manometry allows for the characterization of the type of achalasia, which in turn has important therapeutic implications. The endoscopic management of AC has been reinforced with the introduction of POEM that has been found to be highly effective and safe in palliating the symptoms in short‐term to mid‐term follow‐up studies. POEM is less invasive than Heller's myotomy and provides the endoscopist with the opportunity of adjusting the length and orientation of esophageal myotomy according to the type of AC. The management of achalasia needs to be tailored for each patient, and the role of pneumatic balloon dilatation, POEM, or Heller's myotomy needs to be revisited. In this review, we discuss the important aspects of diagnosis as well as management of AC. The statements presented in the manuscript reflect the cumulative efforts of an expert consensus group.